1997
DOI: 10.1111/j.1651-2227.1997.tb14805.x
|View full text |Cite
|
Sign up to set email alerts
|

High dose vitamin A supplementation in the course of pneumonia in Vietnamese children

Abstract: We carried out a randomized, placebo-controlled, double-blinded trial to evaluate the effect on morbidity of high dose oral vitamin A, given on hospital admission to 592 children aged 1-59 months with moderate and severe pneumonia. Severely underweight children were not included, but 45% were moderately underweight. The vitamin A and placebo groups were comparable in baseline characteristics. Four patients died. Among all of the surviving children, no differences were found regarding mean time for normalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…The effect of vitamin A on respiratory infections has been examined in several randomized clinical trials, with varying results. Most hospital-based studies on vitamin A supplementation and the severity of pneumonia have not shown significant overall effects (36,41,74,97,139), as recently reviewed by Brown and Roberts (21). In fact, some of the hospital-based studies suggest an apparent increase in indicators of severity associated with vitamin A supplementation (41,85,105,146).…”
Section: Vitamin a Supplementation And Clinical Outcomesmentioning
confidence: 78%
“…The effect of vitamin A on respiratory infections has been examined in several randomized clinical trials, with varying results. Most hospital-based studies on vitamin A supplementation and the severity of pneumonia have not shown significant overall effects (36,41,74,97,139), as recently reviewed by Brown and Roberts (21). In fact, some of the hospital-based studies suggest an apparent increase in indicators of severity associated with vitamin A supplementation (41,85,105,146).…”
Section: Vitamin a Supplementation And Clinical Outcomesmentioning
confidence: 78%
“…They all used a placebo group to compare the results and severely malnourished children were most of the time excluded. Except in one study (Julien et al, 1999), no benefits of VA supplementation were reported (Kjolhede et al, 1995;Nacul et al, 1997;Si et al, 1997;Fawzi et al, 1998;Mahalabanis et al, 2004). Adverse effects of high-dose VA were reported in two studies (Stephensen et al, 1998;Fawzi et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…In Vietnam, moderately malnourished VA-supplemented children had a significantly shorter time of hospitalization (Si et al, 1997).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Two additional placebo-controlled studies using higher doses of oilbased vitamin A (400 000 IU over 2 days in children Ͼ1 year of age and half this dose in younger subjects) have been completed recently in Brazil 12 and Vietnam. 13 In Brazil, 472 inpatients and outpatients 6 months to 5 years of age with a clinical diagnosis of pneumonia were studied. Fever, respiratory rate, and blood oxygen saturation were monitored daily in inpatients and on days 3 and 11 in outpatients.…”
Section: Discussionmentioning
confidence: 99%